Reflections on technology, teaching, learning, and professional development: Findings from a teacher survey in Tanzania - Koomar, Saalim; Hennessy, Sara; Zubairi, Asma; Kindoli, Robert; Kreimeia, Adam (African Educational Research Journal, 2022)
This paper presents findings from a survey of 774 government school teachers across Tanzania over the period 2020-2021. The aims were to capture teachers' recent experiences concerning (1) access and use of technology; (2) any student learning losses observed, and teachers' recommendations to address lost learning; and (3) experiences and needs concerning teacher professional development (TPD). Key findings were (1) forty percent of teachers reported that their school lacked access to any form of technological device, with almost half stating they never used digital technologies for teaching and learning purposes. (2) Almost half of the teachers perceived that girls' learning suffered more than boys, and more than 60% of teachers believed learners from the financially poorest households suffered the greatest learning losses. (3) Teachers in Tanzania engaged in very little TPD and wanted increased support. The key differences across teacher groups were further examined by demographic factors, with notable differences apparent between urban and rural teachers, teachers with different levels of experience and different qualification levels. Recommendations are presented to stakeholders across the education ecosystem, including policymakers, school leaders, TPD designers, teachers, and researchers. The findings inform a national technology-mediated TPD programme in Tanzania.
Keywords: Access to Computers; Elementary School Teachers; Faculty Development; Foreign Countries; Gender Differences; Learning Processes; Pedagogical Content Knowledge; Poverty; Public School Teachers; Rural Urban Differences; Secondary School Teachers; Social Differences; Teacher Attitudes; Teacher Characteristics; Teacher Qualifications; Teacher Surveys; Teaching Experience; Teaching Methods; Technological Literacy; Technology Integration; Technology Uses in Education; _r:AddedByZotZen

Sierra Leone Series: Plan International and the importance of community support for distance teacher professional development programmes - McBurnie, Chris; Saidu, Arthur; Rincon Casado, Eusebio; Shergill, Maggie (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Sierra Leone series: Plan International and the importance of community support for distance teacher professional development programmes - Saidu, Arthur; Casado, Eusebio Rincon; Shergill, Maggie; McBurnie, Chris (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.  In week four, we met with Arthur Saidu, Eusebio Rincon Casado and Maggie Shergill from…
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found